Focus on comprehension - Gould, Mike (Learners Pulishing, 2006)
This book contains approximately 30 passages, with focused comprehension tasks that are preceded by the teaching of key comprehension skills. There are 19 main units, each focusing on a different skill or area and 4 summative Practice Unints and a final Review Paper, all designed to prepare students for formal assessments.